DIPLOMASI DAN PERDAGANGAN JASA PENDIDIKAN TINGGI DI ASEAN - , Sheiffi Puspapertiwi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
ASEAN Community 2015 is a significant stepping stone for South East Asia regionalism as it remarks the implementation of common market phase principles by liberalizing production factors movement within region. Since 2007, ASEAN has gradually increased its integration, in which higher education is recognized as strategic issue to increase regional service trade and human development quality. Related to the issue, this research is conducted to understand driving forces behind ASEAN regionalism and its purposes to member countries from higher education perspective by employing qualitative method to collect and analyze data. Research findings show that education globalization and internal dynamics are main driving forces behind ASEAN regionalism, functioning as defensive collective action toward education globalization and harmonization of national interest in socio-economic issues.